2017
DOI: 10.5005/jp-journals-10018-1208
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Diagnosis, and Risk Factors of Helicobacter pylori Infection in Children

Abstract: H. pylori infection is a global public health problem associated with some gastrointestinal diseases in children, especially in developing countries, since prevalence of H. pylori is low in the developed world. Both noninvasive (stool antigen test, urea breath test, and blood test) and invasive (histology, rapid urease test, and microbiological culture) tests have been utilized to detect H. pylori infection. However, a single test is not reliable enough and does not provide accurate enough data to determine H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Helicobacter pylori infection is a common chronic infection affecting about half of human population worldwide and is most often acquired in early childhood [1,2]. Among children, prevalence of the infection widely varies from <10% in some developed countries such as Sweden and Germany to ≥57% in other (mostly developing) countries such as India and Bangladesh [2]. In Bulgarian children aged 1-3 years, the seroprevalence of the infection was 13.5% [3].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori infection is a common chronic infection affecting about half of human population worldwide and is most often acquired in early childhood [1,2]. Among children, prevalence of the infection widely varies from <10% in some developed countries such as Sweden and Germany to ≥57% in other (mostly developing) countries such as India and Bangladesh [2]. In Bulgarian children aged 1-3 years, the seroprevalence of the infection was 13.5% [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary our study found the prevalence of H.pylori to be higher in patients with tertiary level of education, these category of individuals tend to fall under the high or middle social class demographic (civil and public servant), however no statistical significant association was seen. It could be assumed that these well-educated group of individuals had a better health seeking attitude regarding their dyspeptic symptoms than those in the lower socioeconomic class (who could probably be more at risk for this observation, as may be deduced from our A low socioeconomic status has been reported to promote the transmission of H.pylori prevalence and it has been speculated that the spread of the infection may be associated with domestic overcrowding, high housing density as well as sharing of beds especially in developing countries (Oling et al 2015, Whitaker et al 1993, Ozbey et al 2017 ello and his colleagues, in their showed that the lower social class had a significant association with H.pylori (Bello et al, 2018). They proposed that Individuals from the lower socioeconomic class were more likely to be linked with poor education, including poor health education an environment that predisposes to faecal contamination of food and water (Bello et al, 2018).…”
Section: Prevalence Of Helicobacter Pylorimentioning
confidence: 55%
“…Helicobacter pylori infection was also found to be more prevalent in our patients who had either 3 to 4 siblings or more than 4 siblings, however there was no significant association. The number of siblings has been linked with an increased risk of acquiring H.pylori (Peura et al, 2010, Ozbey et al, 2017. This finding suggests that our patients who had a higher number of siblings may have acquired H.pylori in childhood.…”
Section: Prevalence Of Helicobacter Pylorimentioning
confidence: 63%
See 1 more Smart Citation
“…Recently, studies have demonstrated that the PCR can be performed on stool and tissue specimen and assists identify genes related to antibiotic resistance and virulence [59]. Studies have reported that PCR is used to detect bacterium, pathogenic genes, and specific mutations contributed with antimicrobial resistance [60].…”
Section: Pcrmentioning
confidence: 99%